Antigen-specific lymphocytes enhance nitric oxide production in Mycobacterium bovis BCG-infected bovine macrophages - Carpenter, E.; Fray, L.; Gormley, E. (Wiley, 1998)
Nitric oxide (NO) production was evaluated in macrophages isolated from Mycobacterium bovis bacille Calmette-Guerin (BCG)-immunized, and control non- immunized, cattle. Incubation of M. bovis BCG-infected macrophages with recombinant bovine IFN-? led to increased nitrite levels in culture supernatants. It was also demonstrated that NO production by autologous M. bovis BCG-infected macrophages increased in a linear relationship with the number of antigen-specific lymphocytes added to cultures. The elevated NO levels were also associated with increased IFN-? secretion. Treatment of cultures with the NO inhibitor, N-monomethyl L-arginine (L-NMMA), reduced the levels of NO without affecting the metabolic activity of internalized M. bovis BCG. Our results suggest that synthesis of NO may constitute an integral part of the cell-mediated antigen-specific response against M. bovis BCG. However, although the presence of lymphocytes does partially inhibit multiplication of M. bovis BCG in macrophages, it appears that the activity of NO, or the levels produced in monocyte-derived macrophages, may be insufficient to influence the growth of the intracellular mycobacteria.